خروج الرواية الكويتية عن مألوف التقاليد الاجتماعية: رواية سلالم النهار أنموذجا: Departing of Kuwaiti novel for familiar social traditions: Novel of " Salalm Alnahar" Stairs of the Day" As a model - Essyoud, Sabah Abdel-Rrda (SIBAWAYH Arabic Language and Education, 2021)
شكلت رواية (سلالم النهار) صدمة وتجاوزاً لما استقر في الموروث العربي من حيث استباحة محرمات لم يكن للمرأة نصيب فيها ولا سيما المرأة في منطقة الخليج العربي. ولكن الروائية فوزية شويش السالم قد سمحت لنفسها أن تلج في أفعال وتصرفات كان محظوراً على المرأة أن تقحم نفسها فيها واستباحت ما كان ممنوعاً عليها أن تتجاوزه. لأنها أرادت أن تكون صادمة ليس لأعراف المجتمع الخليجي فحسب وإنما لتحاول تغيير نظرة هذا المجتمع لبعض فئاته، وهم هنا فئة البدون، الذين يعاملون على أنهم شريحة أقل مقداراً وحظوة من فئة الأصلاء. وكان عليها أن تكون صعبة المراس وقاسية تجاه الأعراف الاجتماعية كي تغيِّر ما استقر في النفوس. فتوجهت إلى المسكوت عنه (الجنسي) بألفاظ وتعابير خادشة للحياء العام لتنقل معاناة هذه الشريحة بطريقة صادمة علَّه يكون سبباً في التغييرThe novel "Salalim al-Nahar" was a shock and a departure from what was settled in the Arab heritage in terms of permissibility of taboos that a woman did not have a share in it especially woman in the Arab Gulf region. But the novelist Fawzia Shawish Al-Salem allowed herself to engage in actions and behavior that a woman was prohibited from inserting herself in it. Because she wanted to be shocking not just for the mores of the Gulf society but rather, she was trying to change her society`s view of some of its groups especially The Bidoon who treated as a class is less prestigious than the purebreds. She had to be tough and harsh towards social norms to change what settled in the souls. So she headed to the silent (sexual) words and expressions offensive to public modesty to convey the suffering of this social class in a shocking way that may be a cause of change.Keywords: The Kuwaiti novel, The social tradition, Salalm Alnahar, Stairs of the Day, Fawzia Shawish Al-Salem.